Biorefinery of paulownia by autohydrolysis and soda‐anthraquinone delignification process. Characterization and application of lignin. Issue 3 (6th March 2014) - Zamudio, Minerva A.M.; Alfaro, Ascensión; de Alva, Hugo E.; García, Juan Carlos; García‐Morales, Moisés; López, Francisco
Abstract BACKGROUND Lignin is one of the most abundant polymers in nature. Its physical and chemical properties confer it a high potential for various uses including the production of thermoplastic matrices. This work characterized various types of lignin obtained by alkaline delignification of paulownia with soda–anthraquinone. The delignification process was carried out with or without previous autohydrolysis. The products obtained after evaporation or acidification were used to produce polylactic acid–lignin composites. RESULTS Subjecting the raw material to autohydrolysis prior to alkaline delignification provided a spent liquor (black liquor) containing an increased amount of extracted lignin (11.9% more than without autohydrolysis) and possessing a higher calorific value (14 822 kJ kg−1) than in the absence of an autohydrolysis stage. Thermogravimetric analysis revealed a strong impact of the autohydrolysis process, which provided residual delignification fractions containing abundant lignin and no degradation products of polysaccharides or other constituents of the raw material. Mechanical dynamics analysis of composites with lignin contents from 12.5 to 30% revealed an increased elastic (storage) modulus (E'). CONCLUSIONS Soda lignin has appropriate interaction with the polylactic acid, which allows it to be used for obtaining a composite with adequate physical strength characteristics. © 2014 Society of Chemical Industry